Pal Beach Tourism Development in Marinsow Village, North Minahasa Regency - Seska Meily Hermin Mengko; Pearl L. Wenas; Selvie R. Kalele (Journal of Indonesian Tourism and Development Studies, 2018)
This study aims to identify the potential of Pal Beach tourism attraction, identify individual infrastructure and attraction facilities of Pal Beach, and reviewing tourism development of Pal Beach. This research was conducted in the village of Marinsouw, North Minahasa Regency for six months from April to October 2016. This study used a qualitative description. The results on the development of Pal beach tourism object showed that 1). Accessibility (affordability); driveway access to the Pal coastal resorts is damaged and needs to be repaired by resurfacing and widening the road. 2). Attraction; in this case is the cultural attraction that is religious tourism such as Tulude culture which is a tradition of rural communities of Marinsouw on every January 31st should be developed and packaged in a tour package to attract foreign or domestic tourists to more frequently come to the village of Marinsouw and the Pal beach. 3) Amenities (facilities/comfort); there is a needs to build an inn or a cottage accommodation in Pal coastal region, tourism information facilities are necessary to hold art and culture of Marinsouw rural communities, souvenir shops, restaurants, sanitation of toilet, and recreation attraction for entertainment. 4). Ancillary Services (institutional services and promotions); need to be made marketing and promotional information systems of Pal beach tourism with the full support of the Government in promoting Pal beach attraction. Recommendation of this study, the first for North Minahasa Regency Tourism Office is: a). North Minahasa Regency Government through the Department of Tourism and Cultural needs to make a MoU with the state-owned enterprises to build Pal beach attraction. It is a pity if the potential of Pal beach is not developed and promoted as a tourism destination area; b). Need to restructure and mapping the Pal coastal tourist area unit. c). Attract investors to build tourism supporting facilities such as accommodation, tourism information center, souvenir shops, special attraction; d). Prepare human resources in the field of hospitality and tourism attractions to manage Pal beach; e). Increase counseling and training in preparing resources for the development of Pal beach tourism object; and the second for Marinsouw Rural Community is: a). Preserving cultural customs Tulude as a tourist attraction to be promoted; b. Make Masamper dance attractions on certain days in Pal coastal resort; c). Manage local products such as Goroho banana chips, cassava chips, skills for making plastic flower stalks as typical souvenir from Marinsouw village to raise the family economy; d). Raise awareness in maintaining the security and cleanliness around Pal coastal resorts.Keywords: Attractions, Development, Pal Beach.